Project feasibility study YBS bags - Abeleda, Ramon Miguel; Cansana, Arjay Lennard; Palomares, Cedric Matthew; Yam, Alexander Philip
YBS is a product that aims to capture its market by providing a product that not only adapts to the user's lifestyle, but also uses environmentally-friendy materials for those that are conscious of their surroundings. With the standard features of being transformable from a backpack to a messenger bag and having a bag raincoat, YBS plans to launch with two variants where one offers a laptop pouch for office workers and the other is a reversible bag that can offer a different color set depending on the customers mood. After analyzing the market, the group discovered that by targeting schools, companies, bazaars, and retail outlets, YBS can sell 1,230 pieces/year with an increase in 60 pieces every year thereafter. The materials needed to produce the bag include canvas (a soft textile), buckles, zippers, thread, foam, and plastic patterns. Great detail on the amount of materials needed can be found in the technical analysis but the group estimates that a total of P248.15 is needed to produce one bag. It can be assumed that the materials are readily available on the market so no difficulty should arise from procurement. The production process is standard for all bag manufacturing and the process can be broken down into preparation, cutting, decoration, sewing, assembly, and packaging. On the pessimistic side, it should take an average employee 60 minutes to produce one bag. Sewing machines and rotary cutters will be needed to maintain production. With 2 employees working on manufacturing the bags, the group should be able to maintain enough capacity to meet the demand and any market fluctuations that may occur such as the peak season from April to May. For the actual facility, 40 sq. meters was deemed to be sufficient for production and the proposed floor layout can be seen in the technical study. Taking into consideration taxes and all the required benefits for employees, the total cost for the entire project amounts to P3,766,290.60. Considering all the costs in the first two months as the project start-up cost, this amounts to P244,682.86 which can be shouldered by the 4 partners. Additionally, based on project demand the group is expecting to make back its initial investment within the first 5 months and the total net profit over 5 years is projected to be P2,917,430.99. Because the bag can be readily made with the right equipment and because of the sufficient profits generated as well as room for expansion, the group concludes that YBS is feasible.